Severe Symptoms of Mental Disorders Among Students Majoring in Foreign Languages in Vietnam: A Cross-Sectional Study - Thang, Nguyen Thi; Linh, Dao Thi Dieu; Anh, Ta Nhat; Phuong, Nguyen Thị; Giang, Nguyen Duc; Long, Nguyen Xuan; Nhung, Dao Thi Cam; Long, Khuong Quynh (Frontiers in Public Health, 2022)
Mental health disorders among university students have been a serious issue in many countries and can negatively affect academic performance and all aspects of daily living, relationships, and physical health. In this study, we aim to estimate the prevalence of severe symptoms of mental disorders and examine associated factors among students majoring in foreign languages in Vietnam. We used the Depression, Anxiety, and Stress Scales (DASS-21) to detect severe symptoms of mental disorders in 1,788 students, including severe symptoms of depression, anxiety, and stress. The Financial-Study-Family-Friend (FSFF) scale was utilized to assess how much students worried about finance, academic, and social support from family and friends. Multiple logistic regressions were carried out to evaluate the relationship between severe symptoms of mental disorders and FSFF factors. The prevalence of severe levels of depression, anxiety, and stress were 21.1%, 35.0%, and 16.3%, respectively. While varying somewhat due to students’ demographic characteristics, all four aspects of the FSFF scale were related to the severe symptoms of mental disorders of students. Concerns about study had the largest effects (ORs ranging from 2.84 to 3.72) while difficulty in finance had the smallest effects (ORs ranging from 1.23 to 1.37) on students’ depression, anxiety, and stress. The prevalence of severe symptoms of mental disorders in students was high in our study. Teachers and universities should focus more attention on students’ mental health. Social support from family and friends also plays a crucial role in the mental health of students.